Students: Development of an Integrated Letter Information System to Enhance Administrative Efficiency in Villages (UNIB Press, 2024)
This research aims to address administrative challenges and enhance public services in Ringgit Village and Tunjungan Village, Purworejo, Central Java, by developing an integrated information system for village government letter management. Issues such as complicated bureaucracy, lack of transparency, and low efficiency in administration require an innovative approach. By applying the ADDIE method (Analysis, Design, Development, Implementation, Evaluation) and integrating an Application Programming Interface (API), this research aims to improve the efficiency of government letter management and the overall quality of public services. The research limitations include a focus on administration and public services, excluding other fields that are not directly related. The benefits include improved public service quality, increased community participation, and reduced digital divide. It is hoped that this research will make a positive contribution to efforts in community development and empowerment at the local level.